FRI0368 The Use of Ultrasound in The Diagnosis and Management of Patients with Giant Cell Arteritis: Experience of A Single Centre. (15th July 2016) - Ponte, C.B.; Floris, A.; Vaggers, S.; Goodfellow, N.; Sznajd, J.; O'Neill, L.; Piper, J.; Gunn, J.; Mankia, K.; Luqmani, R.A.
Abstract : Background: Giant cell arteritis (GCA), the most common primary vasculitis, can cause irreversible blindness in 20–30% of untreated cases, but glucocorticoid therapy leads to significant toxicity in >80% of patients. Ultrasound has proven to be effective in diagnosing giant cell arteritis (GCA) and has the potential to monitor disease activity. Objectives: We reviewed data on all patients referred to a single university hospital between August 2014 and December 2015 who were seen in a "fast-track" service established to diagnose and evaluate suspected GCA or a suspected flare. Methods: All patients underwent rapid evaluation by a combination of standard clinical assessment and ultrasound of the temporal and axillary arteries. The ultrasound scan was considered positive when we identified the presence of a dark halo around the temporal artery wall or a homogeneous hypoechoic wall thickness >1.5 mm in the axillary arteries. We performed a retrospective analysis and comparison of the ultrasound findings with the clinical features, temporal artery biopsy (TAB) results and decision to treat patients with suspected or established GCA. Results: We performed 206 scans in 169 patients (71% females, mean [SD] age 72 ± 11 years). In 123 cases, patients were referred for suspected GCA: 63% were already receiving high-doses of steroids (mean of 12 ± 10 days); 78% had headache; 60% high inflammatory markers; 33% abnormal vascular examination (e.g. diminished/absent pulse or bruits); 31% scalp tenderness; 28% jaw claudication; 26% polymyalgia rheumatica and 26% visual symptoms. In 39 cases the scan was positive: 9 also had a TAB (4 positive) and all were treated as GCA. In 77 cases the scan was negative: 27 also had a TAB (1 positive) and 9 were treated as GCA. In 7 cases the scan was inconclusive requiring further investigations (e.g. TAB). Patients with a positive scan had a mean CRP of 17.6 ± 30.1 g/dl and a mean ESR of 41.3 ± 43.3 mm/hour; patients with a negative scan had a mean CRP of 13.8 ± 17.9 g/dl and a mean ESR of 16.3 ± 17.6 mm/hour (p=0.979 and p=0.048, respectively). We scanned 83 patients with an established diagnosis of GCA to assess for flare or monitor disease activity: 29 had a positive scan (21 increased medication; 8 were follow-ups with improvement from baseline) and 54 had a negative scan (4 increased medication; 50 allowed a safer taper or withdrawal of glucocorticoids). Patients with a positive scan had a mean CRP of 8.0 ± 10.1 g/dl and a mean ESR of 15.6 ± 17.3 mm/hour; patients with a negative scan had a mean CRP of 9.6 ± 16.9 g/dl and a mean ESR of 20.5 ± 19.3 mm/hour (p=0.970 and p=0.190, respectively). Conclusions: The combination of rapid clinical evaluation and ultrasound were key elements in diagnosis and monitoring of GCA, allowing more flexible use of glucocorticoid dose regimens and reducing the number of TABs required. The only patient with a negative scan but a positive TAB had already received 20 days of glucocorticoids, suggesting that delay in investigation after starting therapy could affect the results of the scan. References: Luqmani RA, et al. The Role of Ultrasound Compared to Biopsy of Temporal Arteries in the Diagnosis and Treatment of Giant Cell Arteritis. Arthritis Rheumatol 2015; 67 (suppl 10) Disclosure of Interest: C. Ponte: None declared, A. Floris Grant/research support from: Italian Society of Rheumatology, S. Vaggers: None declared, N. Goodfellow: None declared, J. Sznajd: None declared, L. O'Neill: None declared, J. Piper: None declared, J. Gunn: None declared, K. Mankia: None declared, R. Luqmani Grant/research support from: GSK, Nordic, Medimmune, Chemocentryx, Roche, UCB, Consultant for: GSK, Nordic, Medimmune, Chemocentryx